2015
DOI: 10.1007/s11356-015-4416-8
|View full text |Cite
|
Sign up to set email alerts
|

What factors drive the variations of phytoplankton, ciliate and mesozooplankton communities in the polluted southern coast of Sfax, Tunisia?

Abstract: We studied the spatial distribution of phytoplankton, ciliate and mesozooplankton communities coupled with environmental factors in the southern coast of Sfax (central eastern coastline of Tunisia). Phytoplankton assemblages were dominated by Dinophyceae (69.99%) and Bacillariophyceae (15.88%). The ciliate community consisted of Spirotrichea with a dominance of Tintinnopsis beroidea (57.69%). The mesozooplankton community was dominated by copepods representing 66.12% of the total zooplankton. Oithona nana show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 94 publications
2
31
1
Order By: Relevance
“…Since the industrialization in 1970, which involves discharge from large-scale phosphate production plants in Sfax and Gabes (Béjaoui et al, 2004;Ghannem et al, 2010), the phosphogypsum discharge (∼12000 ton per day) has become the main cause of the disequilibrium of this ecosystem. Recent studies has shown a decrease in fish resources (Zairi and Rouis, 1999;Hamza-Chaffai and Pellerin, 2003); a loss of marine biodiversity (Drira et al, 2008;Barhoumi et al, 2009;Rabaoui et al, 2013) and a degradation of water quality (Bel Hassen et al, 2008;Drira et al, 2014a, b;Ben Salem et al, 2015). The discharges of phosphogypsum led to a drastic decrease in the seagrass areas, as observed for Posidonia oceanica assemblages, which were shown to be https://doi.org/10.1016/j.ecss.2019.01.006 Received 6 July 2018; Received in revised form 27 September 2018; Accepted 10 January 2019 strongly reduced in the more polluted areas (Béjaoui et al, 2004;Ben Brahim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since the industrialization in 1970, which involves discharge from large-scale phosphate production plants in Sfax and Gabes (Béjaoui et al, 2004;Ghannem et al, 2010), the phosphogypsum discharge (∼12000 ton per day) has become the main cause of the disequilibrium of this ecosystem. Recent studies has shown a decrease in fish resources (Zairi and Rouis, 1999;Hamza-Chaffai and Pellerin, 2003); a loss of marine biodiversity (Drira et al, 2008;Barhoumi et al, 2009;Rabaoui et al, 2013) and a degradation of water quality (Bel Hassen et al, 2008;Drira et al, 2014a, b;Ben Salem et al, 2015). The discharges of phosphogypsum led to a drastic decrease in the seagrass areas, as observed for Posidonia oceanica assemblages, which were shown to be https://doi.org/10.1016/j.ecss.2019.01.006 Received 6 July 2018; Received in revised form 27 September 2018; Accepted 10 January 2019 strongly reduced in the more polluted areas (Béjaoui et al, 2004;Ben Brahim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A striking difference between the north and south coasts is seen in suspended matter concentrations with lower values in the south (23.87-61.44 mg/L), contrasted with the higher concentrations in the north (48.20-201.56 mg/L). The high suspended matter concentration levels may reasonably be attributed to the shallowness of the sampled north stations, the spatial distribution of tiny particles and tidal action [13] and to the recently added soil, not yet fully stabilised. We found low orthophosphate concentrations follow-on phosphogypsum restoration in the north coast of Sfax (0.18-2.60 µmol/L).…”
Section: Discussionmentioning
confidence: 96%
“…On the south coast of Sfax not yet restored, the previous studies focus on the spatial and seasonal distribution of ultraphytoplankton [5], microphytoplankton [5,10,11], ciliates [10,11] and zooplankton [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sfax coast, a part of the Gulf of Gabes, are surely associated to the two industrial regions of Madagascar and Sidi Salem, the sewage treatment station ONAS (National Sanitation Office). These regions are recognized for generating contaminants released from commercial, agricultural and domestic effluents (Ben Salem et al, 2015). The residue of phosphate treatment, phosphogypsum, has been stocked along the coast at an abandoned dumpsite from the plant which fabricates phosphoric acid (SIAPE) (Rekik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%